Portuguese building stock indoor environmental quality “in-situ” assessment - Silva, Pedro Correia Pereira da (2010)
Since the implementation of the Energy Performance of Building Directive, EPBD, in general, and the entrance into force of the respective Portuguese codes, in particular, buildings are requested to have better energy performances. However, during the buildings performance evaluation, energy issues should not be the only concerns since the indoor environmental quality is also as important. Thus, in this paper it is presented an “in-situ” evaluation of the Portuguese building stock regarding several parameters related to indoor environmental quality (IEQ), envelope thermal quality and operating conditions, natural illumination levels, thermal and acoustic comfort and indoor air quality. During the measurement campaign were evaluated several buildings that encompass different types of construction solutions, climatic zones and construction periods. One of the major objectives of this study was to support the development of building solutions that can optimize all the relevant parameters to the IEQ. Another important objective is the dissemination of the results through public entities, such as construction companies and design teams in order to influence the buildings projects to include other parameters than energy during the design process. Even though the measuring campaign is still in progress, there are already some preliminary results that show that, in average, the Portuguese buildings have a poor envelope thermal resistance, untreated thermal bridges, unsuitable natural illumination levels, several problems regarding high concentration of some pollutants like CO2 or VOC and also problems with acoustic discomfort due to an inadequate sound insulation.